Aid, volatility and growth again: When aid volatility matters and when it does not - Lisa Chauvet; Patrick Guillaumont (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
In previous papers we have argued that aid is likely to mitigate the negative effects of external shocks on economic growth (i.e., aid is more effective in countries that are more vulnerable to external shocks). Recently an important debate has emerged about the possible negative effects of aid volatility itself. However, the cushioning effect of aid may involve some volatility in aid flows, which then is not necessarily negative for growth. In this paper we examine to what extent the time profile of aid disbursements may contribute to an increase or a decrease of aid effectiveness. We first show that aid, even if volatile, is not clearly as procyclical as often argued, and, even if procyclical, is not necessarily destabilizing. We measure aid volatility by several methods and assess procyclicality of aid with respect to exports, thus departing from previous literature, which usually assesses procyclicality of aid with respect to national income or fiscal receipts. The stabilizing/destabilizing nature of aid is measured by the difference in the volatility of exports and the volatility of the aid plus exports flows. Then, in order to take into account the diversity of shocks to which aid can respond, we consider the effect of aid on income volatility and again find that aid is making growth more stable, while its volatility reduces this effect. Finally, we find evidence through growth regressions that the higher effectiveness of aid in vulnerable countries is to a large extent due to its stabilizing effect.
Keywords: F35; F43; O42; 330; aid; shocks; stability; growth; Entwicklungshilfe; Volatilität; Schock; Wirtschaftswachstum